Taxonomic studies in the genus Haplanthodes (Acanthaceae) - Deshmukh, Pradip Vikram; Surveswaran, Siddharthan; Gore, Ramchandra Dnyanoba; Lekhak, Manoj Madhwanand (Phytotaxa, 2021)
The endemic Indian genus Haplanthodes (Acanthaceae) is revised. Four species, viz. H. neilgherryensis, H. plumosa, H. tentaculata and H. verticillata and a new variety, H. neilgherryensis var. toranganensis are recognized. Lectotype is designated for Haplanthodes, Haplanthus plumosus and H. verticillaris. The nomenclature of the Linnaean name Ruellia tentaculata is also discussed. Micromorphology of seed using light microscope (LM) and scanning electron microscope (SEM) is observed for the first time, and two types, reticulate and micro papillate, have been recognized based on surface sculpturing pattern. The genus differs from the related genera Andrographis and Haplanthus by distinctly two grooved seeds with hygroscopic hairs. Pollen grains of the genus are oblate or prolate spheroidal, distinctly triangular, trizonocolporate with reticulate exine ornamentation.